Experimental and Computational Study of Mechanical and Thermal Characteristics of h-BN and GNP Infused Polymer Composites for Elevated Temperature Applications - Choukimath M.C.; Banapurmath N.R.; Riaz F.; Patil A.Y.; Jalawadi A.R.; Mujtaba M.A.; Shahapurkar K.; Khan T.M.Y.; Alsehli M.; Soudagar M.E.M.; Fattah I.M.R. (MDPI, 2023)
Bending strength; Boron nitride; Composite materials; Graphene; III-V semiconductors; Loads (forces); Nanocomposites; Reinforcement; Scanning electron microscopy; Thermogravimetric analysis; Computational studies; Epoxy; Graphene nanoplatelets; H-boron nitrides; High-temperature application; Load-bearing capacity; Mechanical characteristics; Polymer composite; Polymer materials; Polymer-based nanocomposites; High temperature applications